The Effectiveness of Local Government Policies in Gayo Coffee Farmers' Welfare during the COVID-19 Pandemic - Ikhsan, Ikhsan; Marefanda, Nodi; Husna, Cut Asmaul; Hajad, Vellayati; Herizal, Herizal (Universitas Muhammadiyah Yogyakarta, 2024)
This study aims to discuss whether local government policies affected the coffee farmers’ welfare during the COVID-19 pandemic. Gayo coffee is a superior commodity that supports the economy of almost 90% of Central Aceh people, so coffee-related policies greatly determine their welfare. The COVID-19 pandemic, on the other hand, has influenced the coffee business globally, which has caused difficulties for farmers selling coffee at a reasonable price, and this condition has affected the Gayo coffee farmers, who have been export-oriented. This study used a qualitative method with a case study approach. The informants in this study consisted of 8 people. Data was collected through interviews and documentation, and then the data was analyzed using data reduction, data display, and conclusion drawing. The results showed that the government of Central Aceh fostered coffee cultivation for farmers, helped open export markets to prevent and protect Gayo coffee farmers from the impact of COVID-19, and assisted business capital. Hence, government policies of Central Aceh have not been able to achieve Gayo coffee farmers’ welfare as seen from the shallow targets and goals made.